Spinocerebellar ataxia type 17 associated with an expansion of 42 glutamine residues in TATA-box binding protein gene - Nolte, Dagmar; Sobanski, E.; Wißen, A.; Regula, Jens Ulrich; Lichy, Christoph; Müller, U. (Journal of neurology, neurosurgery, and psychiatry, 2010)
Background Spinocerebellar ataxia type 17 (SCA17) is caused by abnormal expansions of CAG/CAA trinucleotides within the TATA-box binding protein gene (TBP). The currently accepted critical threshold of abnormal expansions is ≥43. - Objective To investigate the minimal CAG/CAA expansion within the TBP in SCA17. - Results 285 patients with autosomal-dominant ataxia were examined, and abnormal or borderline expansions of CAG/CAA within TBP in eight cases were found. Of those, four patients from three families had exactly 42 CAG/CAA trinucleotides, that is, one codon less than the currently accepted critical threshold of 43. The four patients presented with a relatively benign phenotype. All had dysdiadochokinesia and dysarthria. Mild gait ataxia was observed in three of the four patients. - Conclusion The reference definition of at least 43 CAG/CAA codons for pathological SCA17 alleles should be lowered to 42.
Gesehen am 22.05.2023